Dynamic male mouse gut microbiota signature linked to improved wound healing of a novel salecan hydrogel dressing - Luo, Guangping; Zhang, Tongtong; Jiang, Yanan; Qin, Yuan; Chen, Pengfei; Hu, Junqing (Frontiers in Bioengineering and Biotechnology, 2025)
Salecan-based hydrogel (thereafter called Sal-hydrogel) dressings and gut microbiota have been associated with enhanced wound healing. However, the relationship between these two factors remains unclear. This study investigated the dynamic characteristics of the intestinal microbiota in relation to the Sal-hydrogel dressings and their role in promoting wound healing. Fecal samples were collected at day 0, 3, 7, and 12 after wounds were inflicted on 48 mice, which were treated with either Sal-hydrogel, Staphylococcus aureus, or a combination of S. aureus and Sal-hydrogel, using a full-thickness skin perforation wound model. The samples were subjected to 16S rRNA V3-V4 gene sequencing. The results indicated a general trend for Shannon diversity of the intestinal microbiota to increase by day 3 following injury. On the final day, the diversity in both the hydrogel group and the S. aureus plus hydrogel group was significantly higher compared to the control group (p < 0.05). Additionally, the bacterial community structure in the mouse gut exhibited substantial changes when comparing the hydrogel-treated groups to the controls (hydrogel group: p = 0.027; S. aureus plus hydrogel group: p = 0.039). The genus uncultured_Oscillospiraceae, which was significantly associated with wound closure (R-squared = 0.2154, p = 6.657e-05), was found to be dominant in the gut of the hydrogel group during the wound healing process. Overall, our findings suggest that significant and rapid alterations in gut microbiota occur in response to skin injury and wound infection. The enhanced wound healing properties of the Sal-hydrogel dressing are associated with increased intestinal microbiota diversity and the presence of the bacterium uncultured_Oscillospiraceae.